1988
DOI: 10.1177/36.7.2898495
|View full text |Cite
|
Sign up to set email alerts
|

Complementary distribution of carbamoylphosphate synthetase (ammonia) and glutamine synthetase in rat liver acinus is regulated at a pretranslational level.

Abstract: We studied the distribution of the mRNAs for carbamoylphosphate synthetase (ammonia) and glutamine synthetase in frozen sections of adult rat liver by in situ hybridization to [35S]-labeled cDNA probes. The density of silver grains resulting from hybridization to the labeled cDNA probe for carbamoylphosphate synthetase is highest around the portal venules, decreases towards the central venule, and is virtually absent from an area two to three cells wide that lines the central venules in which mRNA for glutamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 16 publications
4
49
0
Order By: Relevance
“…fig.lB). This finding corroborates the results of a study by Moorman et al [1] who showed that, in rat liver, GS and CPS mRNA have a complementary distribution pattern. The hybridization signal, i.e.…”
Section: Slot Blot and Northern Blot Analysissupporting
confidence: 92%
See 3 more Smart Citations
“…fig.lB). This finding corroborates the results of a study by Moorman et al [1] who showed that, in rat liver, GS and CPS mRNA have a complementary distribution pattern. The hybridization signal, i.e.…”
Section: Slot Blot and Northern Blot Analysissupporting
confidence: 92%
“…Thus, the heterogeneous distribution of GS in rat liver parenchyma seems to be due to differences in gene expression m hepatocytes from different acinar localizations. A similar conclusion was drawn by Moorman et al [1] for rat and by Smith and Campbell [8] for mouse liver based on in situ hybridization only. This interpretation is supported by the results of different experimental approaches such as induction of hepatocyte growth in vitro [13], induction of hepatocarcinogenesis [15], and hepatocyte transplantation [27], suggesting that this unique program of gene expression may be altered only under certain circumstances provided that the hepatocytes have undergone mitosis.…”
Section: 4kbsupporting
confidence: 87%
See 2 more Smart Citations
“…Thus arginine-dependent glutamate synthesis is highly restricted within the liver. As glutamine synthetase is also selectively expressed in perivenous hepatocytes [267,268], the co-expression of all of these enzymes would support the perivenous synthesis of glutamine in the intercellular glutamine cycle proposed by Hau$ ssinger [269].…”
Section: Arginase and Glutamate Synthesismentioning
confidence: 96%